NORWIDOWSKIE POMNIKI LITERATURY - Abriszewska, Paulina (Colloquia Litteraria, 2017)
Norwidian Literary Monuments The article discusses functions of quoting pre-Romantic authors in Norwid’s literary and discursive texts. The author argues that Norwid treated Franciszek Karpiński, Piotr Skarga, and Ignacy Krasicki as commentators of the nineteenth-century world and consequently as ‘literary monuments’ who participated in forging the contemporary cultural reality. In Norwid’s works, these authors themselves, not only their texts, became sui generis manifestations and figures of the fate of an unanswered prophet, or an advocate of home truths; as such they became mythologised. One can also find in Norwid’s works, however, elements of the discussion with literary tradition, which proves that he actively engaged with some of the ‘monuments’ of literature (cf. the case of Łukasz Górnicki).